Mechanical property and adhesion strength of carbon nanofillers reinforced alumina single splats using in-situ picoindentation and nanoscratch test. Issue 19 (1st October 2021) - Pandey, Krishna Kant; Shukla, Dipak Kumar; Verma, Rahul; Keshri, Anup Kumar
Abstract: Current study deals with the effect of carbon nanotube (CNTs) and graphene nanoplatelets (GNPs) reinforcement on the mechanical properties and the adhesion strength of plasma sprayed alumina (Al2 O3 ) single splats, using in-situ picoindentation and nanoscratch test, respectively. The hardness of the Al2 O3 splat was measured as 18 ± 5.3 GPa which increased to 34.22 ± 8.44 GPa on 1 wt% CNTs addition and to 42.5 ± 9.06 GPa on 0.5 wt% GNPs addition. Hybrid addition of CNTs and GNPs provided the maximum hardness value of 51.25 ± 8.76 GPa to the Al2 O3 splat. Similar trend in the elastic modulus has been reported with a minimum value for Al2 O3 splat, i.e. 159 ± 35.40 GPa, and maximum for the Al2 O3 splat mixed synergistically with CNTs and GNPs (269 ± 43.12 GPa). Adhesion strength of the Al2 O3 splat (0.21 ± 0.11 MPa) also showed a nearly 5-fold increase on hybrid addition of CNTs and GNPs with a maximum value of 1.08 ± 0.38 MPa. This improvement in the properties were due to the extremely high mechanical properties of CNTs and GNPs and better melting of the splats, which not only improved the densification but also provided a better interlocking between the splat and the substrate.